What Do Chinese Families With Depressed Adolescents Find Helpful in Family Therapy? A Qualitative Study - Liu, Liang; Wu, Jiajia; Wang, Jing; Wang, Yan; Tong, Yuezhou; Ge, Congcong; Wang, Yanbo (Frontiers in Psychology, 2020)
Despite research supporting the efficacy of family therapy for adolescent depression, little research has been done to clarify the therapeutic variables that Chinese families with depressed adolescents consider helpful in family therapy. This study explored Chinese depressed adolescents’ and their parents’ perceptions of the factors promoting improvement in family therapy. Twelve Chinese families with one adolescent child fulfilling the criteria for major depressive disorder were recruited. A total of 134 family therapy sessions were conducted by 4 therapists. After therapy, semi-structured interviews about the clients’ perceptions of the helpful and effective aspects of therapy were conducted. Thematic analysis was used to analyze the transcribed dialogues. Five overarching themes emerged: factors supporting therapeutic alliance formation, the therapist’s systemic attitude, systemic therapy direction, effective systemic therapy techniques and strategies for dealing with current issues. A trustworthy therapy alliance with a competent and supportive therapist helped depressed adolescents improve by facilitating the expression of their emotions; exploring family interactions, beliefs and emotion flows related to their symptoms; promoting their self-development; and activating their resources. The families valued the respectfulness of the therapists and their collaborative and nonauthoritative approach. Adolescents’ academic difficulties and crises received special attention. The possible clinical implementations of our findings in the design of family therapy strategies for depressed Chinese adolescents are discussed.